Second primary non-myeloid malignancies following intensive treatment for adult acute myeloid leukaemia: a Danish population-based cohort studyResearch in context - Nanna Nørtoft Nielsen; Jonas Faartoft Jensen; Joachim Baech; Trine Trab; Tarec Christoffer El-Galaly; Claudia Schöllkopf; Andreas Due Ørskov; Hans Beier Ommen; Lene Sofie Granfeldt; Daniel Tuyet Kristensen; Marianne Tang Severinsen (The Lancet Regional Health. Europe)
Summary: Background: Second primary malignancies (SPMs) are a well-known, long-term complication of antineoplastic treatment. This nationwide cohort study examined the risk of non-myeloid SPMs in survivors of adult acute myeloid leukaemia (AML) treated with intensive chemotherapy and, in some cases, allogeneic stem cell transplantation (alloSCT), compared to a matched general population. Methods: Patients with incident AML between 2000 and 2018, alive and aged 18–70 years two years after start of intensive chemotherapy, were included and matched 1:10 to comparators from the general Danish population on sex, age, and the Nordic Multimorbidity Index. Exclusion criteria were non-myeloid SPMs for both AML survivors and comparators. Findings: A total of 750 AML survivors and 7500 comparators were followed for a median of 10.6 years. The hazard ratio (HR) of non-myeloid SPMs was 1.55 (95% confidence interval [CI] 1.27–1.89) for AML survivors compared to comparators, driven by non-melanoma skin cancer (HR 2.52, 95% CI 1.90–3.35), not of solid cancer (HR 1.14, 95% CI 0.87–1.49). The 10-year cumulative incidences of any non-myeloid SPM were 13.5% (95% CI 10.6–16.5%) in AML survivors and 11.9% (95% CI 11.1–12.8%) in matched comparators. Additionally, AML survivors consolidated with alloSCT had a higher hazard rate of non-myeloid SPMs compared to non-transplanted AML survivors (adjusted HR 1.50, 95% CI 1.00–2.26). Interpretation: The increased rate of non-myeloid SPMs observed in this population-based cohort study of AML survivors was almost entirely driven by non-melanoma skin cancer and is thus outweighed by the importance of intensive chemotherapy. Funding: Svend Andersen, Heinrich Kopps, and Karen Elise Jensen’s Foundation.